Content of Carotenoids, Violaxanthin and Neoxanthin in Leaves of Triticum aestivum Exposed to Persistent Environmental Pollutants - Ocsana Opriş; Florina Copaciu; Maria Loredana Soran; Ülo Niinemets; Lucian Copolovici (Molecules, 2021)
Persistent pollutants such as pharmaceuticals, pesticides, musk fragrances, and dyes are frequently detected in different environmental compartments and negatively impact the environment and humans. Understanding the impacts of diffuse environmental pollutants on plants is still limited, especially at realistic environmental concentrations of contaminants. We studied the effects of key representatives of two major classes of environmental pollutants (nine different antibiotics and six different textile dyes) on the leaf carotenoid (violaxanthin and neoxanthin) content in wheat (Triticum aestivum L.) using different pollutant concentrations and application times. The wheat plants were watered with solutions of selected environmental pollutants in two different concentrations of 0.5 mg L−1 and 1.5 mg L−1 for one week (0.5 L) and two weeks (1 L). Both categories of pollutants selected for this study negatively influenced the content of violaxanthin and neoxanthin, whereas the textile dyes represented more severe stress to the wheat plants. The results demonstrate that chronic exposure to common diffusively spread environmental contaminants constitutes significant stress to the plants.